Comparison between a new computer program and the reference software for gray‐scale median analysis of atherosclerotic carotid plaques. Issue 3 (28th May 2014) - Casella, Ivan Benaduce; Fukushima, Rodrigo Bono; Marques, Anita Battistini de Azevedo; Cury, Marcus Vinícius Martins; Presti, Calógero
ABSTRACT Purpose To compare a new dedicated software program and Adobe Photoshop for gray‐scale median (GSM) analysis of B‐mode images of carotid plaques. Methods A series of 42 carotid plaques generating ≥50% diameter stenosis was evaluated by a single observer. The best segment for visualization of internal carotid artery plaque was identified on a single longitudinal view and images were recorded in JPEG format. Plaque analysis was performed by both programs. After normalization of image intensity (blood = 0, adventitial layer = 190), histograms were obtained after manual delineation of plaque. Results were compared with nonparametric Wilcoxon signed rank test and Kendall tau‐b correlation analysis. Results GSM ranged from 00 to 100 with Adobe Photoshop and from 00 to 96 with IMTPC, with a high grade of similarity between image pairs, and a highly significant correlation (R = 0.94, p < .0001). Conclusions IMTPC software appears suitable for the GSM analysis of carotid plaques. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:194–198, 2015;